Reputation: 195
While solving the complexity of a code, I found it as O(log(n!)). I know that this can be proven equal to O(n*log(n)). However, can someone tell where this proof is going wrong?
Theorems used:
Proof
O(log(n!)) = O(log(n*(n-1)*(n-2)*...*2*1))
= O(log(n) + log(n-1) + ... )
= O(max(logn, log(n-1), ...))
= O(log(n))
Can someone tell where I'm going wrong?
Upvotes: 2
Views: 138
Reputation: 10161
You cannot say O(log(n) + log(n-1) + ... ) = O(max(logn, log(n-1), ...))
This is only true for a constant number of summands. In your case the number depends on n.
Otherwise you could also proof
O(n)=O(1+1+1+1+1+...1) = O(max(1,1,1,...))= O(1)
Upvotes: 4